ANALYSIS OF THE EFFECT OF FINANCIAL LITERACY, FINANCIAL TECHNOLOGY, AND INCOME ON FINANCIAL BEHAVIOR - Fitri Yesica Sabrina Panjaitan; Kumba Digdowiseiso (Jurnal Ekonomi, 2023)
The purpose of this study was to determine the effect of financial literacy on financial technology and income on financial behavior (Case Study of a Lecturer in the Faculty of Economics and Business at a Private University in Jakarta). This type of research is quantitative research in which the research subject is a lecturer at the Faculty of Economics and Business (FEB) of a private university in Jakarta. While the object of research is financial behavior which is influenced by financial literacy, Financial Technology, and income. With the sample size taken as many as 40 respondents. The results of this analysis show that financial literacy has a significant influence on financial behavior. So it can be concluded that financial literacy has a positive and significant impact on financial behavior. Financial Technology has a significant influence on financial behavior. So it can be concluded that financial technology has a positive and significant influence on financial behavior. Income has a significant influence on financial behavior. So it can be concluded that income has a positive and significant influence on financial behavior.